Decomposing cover crops modify root-associated microbiome composition and disease tolerance of cash crop seedlings. (September 2021) - Liu, Xiaojiao; Hannula, S. Emilia; Li, Xiaogang; Hundscheid, Maria P.J.; klein Gunnewiek, Paulien J.A.; Clocchiatti, Anna; Ding, Wei; de Boer, Wietse
Abstract: The assembly of root-associated microbes during the seedling stage has strong impact on subsequent performance of crops. Major factors influencing this assembly are crop species identity and composition of potential root-colonizing microbes in the bulk soil. The latter can be modified by soil management, such as organic amendments. The incorporation of residues of cover crops before the start of the growing season of cash crops presents an interesting option for steering of root-associated seedling microbiomes as there is a wide range of cover crops species with different properties available for farmers. In a greenhouse study, we examined the effect of soil amendments with milled shoot and root materials of seven cover crop species (niger seed, phacelia, rapeseed, radish, vetch, black oat and buckwheat) on the assembly of root-associated bacteria and fungi of seedlings of four cash crop species (asparagus, carrot, onion and sugar beet). Field-grown cover crops material used for the study was collected at two time points (before and after winter) which had strong impact on plant elemental composition. The soil used for the study was a mixture of sandy arable soils with a history of soil-borne fungal diseases ( Fusarium and Rhizoctonia ). Within the context of a strong selection of root-associated microbes by cash crop species, we found significant modifying effects by cover crop materials. We show that cover crop elemental composition had a stronger effect than cover crop species identity. High quality residues (with low C/N ratio) caused profound shifts within root-associated Proteobacteria and increases in relative abundance of certain microbial groups such as Bacillaceae and Mortierellomycetes. These changes coincided with differences in establishment and survival of cash crop seedlings. Tolerance of sugar beet seedlings against the fungal pathogen Rhizoctonia solani was correlated with residues causing increases of root-associated Oxalobacteraceae, Bacillaceae and Mortierellaceae. However, the same residues increased Fusarium -induced failure of asparagus seed germination. This indicates that fine-tuning of cover crops amendments for different cash crops is required to realize enhanced functioning of root microbiomes. Highlights: Decomposing cover crop residues alter cash crop seedling root microbiomes. Elemental composition of cover crops is the major factor affecting cash crop root microbial assembly. Differential effects of cover crop quality were seen for different damping-off diseases. Fine-tuning of cash-cover crop combinations is needed when steering beneficial root microbiomes.